2022
DOI: 10.3390/molecules27051519
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Natural Products II

Abstract: Natural products of different origin and their potential therapeutic activities are of unceasing widespread interest to many scientific teams from all around the world [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In recent years, natural products have shown great potential with regard to antibacterial, anti-oxidation, and anti-tumor activity [ 22 ]. An increasing number of studies have demonstrated that PIC exhibits excellent biological activity, such as anti-inflammatory and anti-tumor activity [ 16 , 17 , 23 , 24 ], and is expected to be a natural product that solves many medical problems in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, natural products have shown great potential with regard to antibacterial, anti-oxidation, and anti-tumor activity [ 22 ]. An increasing number of studies have demonstrated that PIC exhibits excellent biological activity, such as anti-inflammatory and anti-tumor activity [ 16 , 17 , 23 , 24 ], and is expected to be a natural product that solves many medical problems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, natural products have shown great potential with regard to antibacterial, anti-oxidation, and anti-tumor activity [22]. An increasing number of studies have…”
Section: Discussionmentioning
confidence: 99%
“…These molecules show multifunctional properties, such as anticancer, antioxidant, antimicrobial, antifungal, and antiviral activities. They also exhibit many beneficial effects on the treatment of neurological, cardiovascular and metabolic, immunological, inflammatory, and related diseases [ 3 ]. According to the World Health Organization, approximately 19 million people were newly diagnosed with cancer in 2020, with a total of 10 million cancer-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are chemically and structurally diverse and possess various biological activities, often with low toxicity and few side-effects (3). They can be obtained from a wide variety of sources, such as plants, microorganisms, algae, fungi, lichens and animals (3,4). Toxins and poisons from animals, mainly amphibians, are also used as alternative medicines (2), and ~47 species of amphibians are recognized for their medicinal use (5).…”
Section: Introductionmentioning
confidence: 99%